Sodium content in commonly consumed foods and its contribution to the daily intake - Calliope, Sonia Rosario (2020)
Salt consumption in many countries of the world exceeds the level recommended by WHO (5 g/day), which is associated with negative effects on health. Public health strategies to achieve the WHO’s objectives include salt content monitoring, improved nutritional labelling and product reformulation. This study aimed to determine the sodium content in street food (SF), fast foods (FF) and artisanal foods (AF) of the Northwest of Argentina, which is not regulated. Moisture, ash and sodium were determined according to the Official Methods of Analysis (AOAC) in 189 samples from each of the three categories. The average and range values were: SF 520 (R: 74-932); FF 599 (R: 371-1093) and AF 575 (R: 152-1373) mg Na/100 g. Thus, general sodium content is high, which means that the consumption of a serving from most of the studied foods leads to an individual exceeding the recommended daily intake values. This study contributes to the knowledge of sodium content in evaluated foods and its contribution to the population intake. This reinforces the importance of implementing new public policies and regulations, advising consumers to check food nutritional labels andselect foods lower in salt content, raising food manufacturers’ awarenessabout the importance of reducing sodium content in foods they produce and in public health.